School Principals Managing Policy Change: The Case of Religion Policy. Issue 1 (2nd January 2020) - Nthontho, Maitumeleng Albertina
Abstract: In 2003, the Department of Education in South Africa promulgated certain religion policy changes. As a result, Religion Education was introduced in schools to replace Religious Education. Since then, religion in schools has been a complex and contested subject. While acknowledging these contestations, this article focuses on the management strategy the twelve purposively selected school principals (hereafter referred to as principals) adopted in implementing religion policy changes in schools. The findings show that two forms of mediation, namely problem-solving and transformative mediation, play an important role in managing the implementation of religion policy changes in schools.